Psychometric Properties of the Competencies Compound Inventory for the Twenty-First Century - Celume, Macarena-Paz; Maoulida, Haïfat (Frontiers in Education, 2022)
The world is evolving rapidly, implying that the jobs of tomorrow, the socio-economic problems and the technologies we will have to interact with, will no longer exist. For this, a new set of skills and competencies will be necessary and these will allow us to face the twenty-first century. The “Four-Dimensional Education” model from the Center of Curriculum Redesign (CCR), which is developed by Fadel and his collaborators in 2015, stands out by proposing a framework that organizes twelve competencies for the twenty-first century, defines them in a clear and usable way, and provides levels for action for all education stakeholders. Based on this model, a self-reported scale was built to assess these competencies. The purpose of this study is to present the psychometric properties of this scale with the objective of measuring this specific set of competencies. The results showed good psychometric properties, presenting a sensitive, reliable, and valid scale to measure twenty-first century competencies.